2007
DOI: 10.1016/j.virol.2007.02.013
|View full text |Cite
|
Sign up to set email alerts
|

How adenovirus strives to control cellular gene expression

Abstract: Host cell gene expression during the course of a human adenovirus infection in synchronized primary human lung fibroblasts was analyzed using cDNA microarrays. The slow progression of the infectious cycle in these cells allowed a detailed examination of cellular gene regulation. In total, 988 unique genes were identified as differentially expressed more than 2-fold. The cellular gene expression profiles closely correlated to the progression of the infection. Based on the observed expression patterns, the dereg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
62
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(74 citation statements)
references
References 71 publications
12
62
0
Order By: Relevance
“…Cellular RNAs that specify proteins implicated in progression through the cell cycle and proliferation have been observed to increase substantially in concentration following Ad5 infection of quiescent human foreskin and lung fibroblasts and the diploid fibroblast line WI38 (51,66,94). Comparison of the alterations in expression of such genes, particularly as exemplified by cyclin E1, induced by infection with Ad5 or the E1B mutant Adhz60 or dl1520 (Onyx-015), led to the conclusion FIG.…”
Section: Discussionmentioning
confidence: 97%
“…Cellular RNAs that specify proteins implicated in progression through the cell cycle and proliferation have been observed to increase substantially in concentration following Ad5 infection of quiescent human foreskin and lung fibroblasts and the diploid fibroblast line WI38 (51,66,94). Comparison of the alterations in expression of such genes, particularly as exemplified by cyclin E1, induced by infection with Ad5 or the E1B mutant Adhz60 or dl1520 (Onyx-015), led to the conclusion FIG.…”
Section: Discussionmentioning
confidence: 97%
“…Recent gene expression analysis has confirmed that infection of normal human cells with group C adenoviruses causes changes in the expression of vast numbers of genes (at least 1,000-2,000) and that many of these genes are involved in the control of the cell cycle (10,11). Genes related to S-phase induction (including cyclins D2 and E1/2, cdk4, and cdk2) were prominent, and our results are entirely in keeping with this, emphasizing the importance of the G 1 -S transition for viral function.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown its therapeutic potential in ovarian cancer (9), and a phase I trial in women with relapsed ovarian cancer is imminent. Efficient production of viral progeny necessitates profound modulation of host cell gene transcription (10,11). The adenovirus must force the cell into S phase to ensure optimal conditions for viral replication while counteracting antiviral defense and cell death mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…A number of reports have shown that adenovirus infection leads to alterations in the transcription of several hundreds, if not thousands, of genes. The differentially expressed genes belong to several Gene Ontology groups and are altered during various stages of viral infection (33,47). One of the genes that are downregulated during adenovirus infection is MYC (27,47).…”
mentioning
confidence: 99%